Gene analysis of multiple oral bacteria by the polymerase chain reaction coupled with capillary polymer electrophoresis. Issue 5 (14th January 2016) - Liu, Chenchen; Yamaguchi, Yoshinori; Sekine, Shinichi; Ni, Yi; Li, Zhenqing; Zhu, Xifang; Dou, Xiaoming
Abstract : Capillary polymer electrophoresis is identified as a promising technology for the analysis of DNA from bacteria, virus and cell samples. In this paper, we propose an innovative capillary polymer electrophoresis protocol for the quantification of polymerase chain reaction products. The internal standard method was modified and applied to capillary polymer electrophoresis. The precision of our modified internal standard protocol was evaluated by measuring the relative standard deviation of intermediate capillary polymer electrophoresis experiments. Results showed that the relative standard deviation was reduced from 12.4–15.1 to 0.6–2.3%. Linear regression tests were also implemented to validate our protocol. The modified internal standard method showed good linearity and robust properties. Finally, the ease of our method was illustrated by analyzing a real clinical oral sample using a one‐run capillary polymer electrophoresis experiment.